Women, capitalism and education: On the pedagogical implications of postfeminism. Issue 7 (7th June 2019) - Öchsner, Marco; Murray, Georgina
Abstract: We examine the emergence of the 'postfeminist' sensibility from feminist theory and praxis, and its relation and relevance to education. Analytical frameworks such as postfeminism and intersectionality have given equal weight to recognition-based struggles, such as those based on sexual, racial, class-based, gender-related identities. We follow Nancy Fraser's argument that these identity-based movements have been co-opted by neoliberal politicians and bureaucratic policy-makers, and become a divide and rule strategy, neglecting the subjugating power of capital. Beginning with third-wave feminism's emphasis on individual identity, women's struggles have been become a part of the greater parisitic neoliberal project. We consider the implications of this docile and domesticated feminism for the education of women.